2012
DOI: 10.3109/02713683.2012.700755
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Analysis of Intraocular Pressure Pulse Wave in Open Angle Glaucomas and Healthy Eyes

Abstract: It is possible to determine spectral components of the IOP pulse wave up to the fifth harmonic by a spectral analysis of dynamic contour tonometry continuous readings. We found that high Ocular Pulse Amplitude values in primary open angle glaucoma group was associated with high harmonics amplitude, which indicates low rigidity of blood vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…Spectral analysis of the ocular pulse amplitude reported by dynamic contour tonometry had shown statistical differences between subjects with different types of glaucoma [19], [26]. Statistically significant differences were found between the harmonics of patients with primary open angle glaucoma and normal tension glaucoma, which may lead to newer diagnostic measures for identifying glaucoma suspects [19]. Age was not significantly correlated with any of the variables in this study and in past studies with other variables [27], [28].…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Spectral analysis of the ocular pulse amplitude reported by dynamic contour tonometry had shown statistical differences between subjects with different types of glaucoma [19], [26]. Statistically significant differences were found between the harmonics of patients with primary open angle glaucoma and normal tension glaucoma, which may lead to newer diagnostic measures for identifying glaucoma suspects [19]. Age was not significantly correlated with any of the variables in this study and in past studies with other variables [27], [28].…”
Section: Discussioncontrasting
confidence: 55%
“…These studies have highlighted salient features of the ORA waveform that could be useful for diagnosis of disease, e.g., a wider area under 1st or 2nd peak indicated a weaker cornea as the weaker cornea deformed slowly [17], [18]. Spectral analysis of the ocular pulse amplitude reported by dynamic contour tonometry had shown statistical differences between subjects with different types of glaucoma [19], [26]. Statistically significant differences were found between the harmonics of patients with primary open angle glaucoma and normal tension glaucoma, which may lead to newer diagnostic measures for identifying glaucoma suspects [19].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a small study of 10 normal subjects and 10 untreated glaucoma patients, they showed that the 2nd, 3rd and 4th harmonic components of the IOP pulse wave were significantly different between the groups. Recently, Božić and colleagues [17] have performed a similar study including a control group of 20 subjects and two groups of glaucoma patients including 20 with primary open angle glaucoma and 20 with normal tension glaucoma. There again, the spectral content of the intraocular pressure pulse wave, measured with DCT, showed differences between the groups.…”
Section: Introductionmentioning
confidence: 99%